(untitled) (Medical Forum Monthly, 2024)
Objective: To assess restoration of finger functions after hemi-hamate reconstruction. Study Design: Experimental / Analytic study Place and Duration of Study: This study was carried out at two different centres at Jinnah Hospital, Lahore and King Khalid Hospital, Najran KSA from between 2010 and 2013. Materials and Methods: We performed hemi-hamate autograft arthroplasty in 20 patients age 16-45 years. All were having comminuted metaphyseal fracture of volar surface of middle phalynx involving more than 50% (55%-90% average 70%) of articular surface with dorsally displaced unstable proximal interphalyngeal joint. Functional outcome was assessed by grip strength, proximal interphalyngeal joint, distal interphalyngeal joint range of motion and residual pain and patient’s satisfaction. Results: At the end of average 24.4 months follow-up mean active range of motion for proximal interphalyngeal joint was 62 °(40°- 90°), distal interphalyngeal joint was 54°(40°-65°) and flexion contracture was 15°(0°-35°).Grip strength was achieved upto 95% (50%-95%) of opposite normal hand. Almost all patients were satisfied with functional outcome and appearance of the finger. We had not come across donor site morbidity, graft resorption, avascular necrosis, subluxation/dislocation, coronal/sagittal instability, infections except 4 patients, one scar tenderness, one ulnar digital nerve paresthesia and 2 with early osteoarthritic changes. Conclusion: Non-vascularized hemi-hamate autogarft is a good treatment option for comminuted proximal interphalyngeal fracture dislocation having more than 50% volar lip involvement, resulting in satisfactory functional outcome as compared to other surgical treatments. We recommend it in patients of active age group.